Culinary Workshop as a Competitive Advantage of Tourism Industry in the South Karelia Region of Finland - Lvov, Anatoly (Saimaan ammattikorkeakoulu, 2014)
Culinary workshop is a new form of modern hospitality industry, which combines modern knowledge in tourism industry with culinary tourism. This project is based on the interest of the consumer and his desire to learn something new, get and experience gastronomy traditions through travelling for culinary workshop. Mission of this project is to convey to the consumer new knowledge, new skill, new interest, opportunities in life through culinary art. Culinary workshops will be described and analyzed in three dimensions: - Culinary workshop as a business project - new product for customers of a hotel and a restaurant; - Culinary workshop as a professional master class; - Culinary workshop as a place of intense social and cultural communication. Results of the thesis work will become the basis for future development of culinary workshops as a business.